Redistribution of the Density of States Due To Coulomb Interactions in La2-2x Sr1+2x Mn2 O7 - Mazur, Daniel; Özyüzer, Lütfi; Gray, Kenneth E.; Zasadzinski, John F.; Özyüzer, Lütfi; Beloborodov, Igor S.; Zheng, H.; Mitchell, J. F. (American Physical Society, 2007)
Tunneling data on La1.28 Sr1.72 Mn2 O7 crystals confirm Coulomb interaction effects through the E dependence of the density of states. Importantly, the data and analysis at high energy E show a pileup of states: most of the states removed from near the Fermi level are found between ∼40 and 130 meV, from which we infer the possibility of universal behavior. The agreement of our tunneling data with recent photoemission results further confirms our analysis.
Keywords: Tunneling (Physics); Strongly correlated electron systems; Fermi wavelength; Coulomb interactions